Increased Postoperative Manual Knee Laxity at 2 Years Results in Inferior Long-term Subjective Outcome After Anterior Cruciate Ligament Reconstruction. Issue 11 (September 2018) - Sundemo, David; Sernert, Ninni; Kartus, Jüri; Hamrin Senorski, Eric; Svantesson, Eleonor; Karlsson, Jón; Samuelsson, Kristian
Background: Increased postoperative rotatory knee laxity after anterior cruciate ligament (ACL) reconstruction may be associated with an increased risk of osteoarthritis and inferior subjective outcome, although long-term studies are lacking. In terms of anteroposterior knee laxity, this association has not yet been established. Purpose/Hypothesis: The purpose was to investigate whether postoperative knee laxity is associated with inferior long-term outcome in patients who have undergone ACL reconstruction. The hypothesis was that increased laxity would cause an inferior long-term clinical and radiographic outcome. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 193 patients underwent ACL reconstruction and were examined at both 2 and 16 years postoperatively. At the 2-year follow-up, knee laxity was tested by use of the Lachman test, the anterior drawer test, the pivot-shift test, and the KT-1000 arthrometer. Outcome variables examined at the 16-year follow-up involved a radiographic assessment of osteoarthritis, patient-reported outcome measurements, and the single-legged hop test. Results: At the long-term follow-up, 147 (76%) patients were examined. The mean follow-up period for the included patients was 16.4 ± 1.2 years. A negative Lachman test at 2 years resulted in a superior International Knee Documentation Committee (IKDC) score (76.3 ± 19.4 vs 67.8 ± 19.3, P < .05) and Lysholm score (85.2 ± 11.9 vs 76.9 ± 17.8, P < .05) at the 16-year follow-up. Correspondingly, a negative anterior drawer test at 2 years was associated with a superior IKDC score (75.3 ± 18.7 vs 62.9 ± 20.2, P < .05) and Lysholm score (84.1 ± 12.1 vs 72.6 ± 20.2, P < .05) at 16 years. A negative pivot-shift test resulted in a superior IKDC score (74.5 ± 18.8 vs 46.9 ± 17.8, P < .05), a superior Lysholm score (83.3 ± 13.4 vs 58.9 ± 23.0, P < .05), and an increased level of activity (Tegner activity scale, median [range]: 4 [1-10] vs 3 [0-5], P < .05). Osteoarthritis was overrepresented in patients with positive manual knee laxity tests, but the difference was not statistically significant. The KT-1000 arthrometer result was not correlated with any outcome variables assessed in this study. Conclusion: Increased manual anteroposterior and rotatory knee laxity 2 years after ACL reconstruction is associated with an inferior long-term subjective outcome.